2023
DOI: 10.1002/slct.202203377
|View full text |Cite
|
Sign up to set email alerts
|

Deep Red to NIR Emitting Xanthene Hybrids: Xanthene‐Hemicyanine Hybrids and Xanthene‐Coumarin Hybrids

Abstract: Xanthene dyes exhibit remarkable photophysical properties and photostability. Their ability to switch fluorescence on/off depending on the external environment makes them a promising candidate for imaging/sensing/tracking/labeling probes. However, their emission � 600 nm and Stokes shift ∼ 34 nm restrict their use in biological applications. A wellknown approach to shifting the emission of xanthene dyes in the deep red to Near infrared (NIR) is by forming xanthene hybrids. This review gives a comprehensive lis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 156 publications
0
6
0
Order By: Relevance
“…In 1996, Czerney et al pioneered the design and construction of the first hybrid fluorophore (merocyanine A), with a maximum absorption wavelength of approximately 700 nm. [23] The hybrid fluorophore was created by integrating xanthene and hemicyanine into an olefinic bond (Figure 2). [33] [24][25][26][27][28][29] and enable fluorescence off-on switching mode.…”
Section: Xanthene-cyanine Conjugated Hybrid Fluorophoresmentioning
confidence: 99%
See 4 more Smart Citations
“…In 1996, Czerney et al pioneered the design and construction of the first hybrid fluorophore (merocyanine A), with a maximum absorption wavelength of approximately 700 nm. [23] The hybrid fluorophore was created by integrating xanthene and hemicyanine into an olefinic bond (Figure 2). [33] [24][25][26][27][28][29] and enable fluorescence off-on switching mode.…”
Section: Xanthene-cyanine Conjugated Hybrid Fluorophoresmentioning
confidence: 99%
“…The hybridization of xanthene and cyanine greatly improved the absorption and emission wavelengths of the fluorophores (Figure 4), but their performance remained insufficient, such as the Stokes shift (Table 1). To solve this problem, in 2013, Lin et al reported a series of xanthene-coumarin hybrid fluoro- [23,34] Figure 3. Molecular structures of xanthene-cyanine conjugated hybrid fluorophores.…”
Section: Xanthene-coumarin Conjugated Hybrid Fluorophoresmentioning
confidence: 99%
See 3 more Smart Citations